Anammox Bacteria Are Potentially Involved in Anaerobic Ammonium Oxidation Coupled to Iron(III) Reduction in the Wastewater Treatment System - Yang, Xiao-Ru; Li, Hu; Su, Jian-Qiang; Zhou, Guo-Wei (Frontiers in Microbiology, 2021)
Anaerobic ammonium oxidation coupled to nitrite reduction (termed as Anammox) was demonstrated as an efficient pathway to remove nitrogen from waste-water treatment system. Recently, anaerobic ammonium oxidation was also identified to be linked to iron(III) reduction (termed Feammox) with either dinitrogen, nitrite or nitrate as end-product, reporting to enhance nitrogen removal from the waste-water treatment system. However, little is known about the role of Anammox bacteria in the Feammox process. Here slurry from waste water reactor amended with ferrihydrite was employed to investigate activity of Anammox bacteria in the Feammox process using 15N isotopic tracing technique combined with 16S rRNA gene amplicon sequencing. Significantly positive relationship between rates of 15N2 production and iron(III) reduction indicated the occurrence of Feammox during incubation. Relative abundances of Anammox bacteria including Brocadia, Kuenenia, Jettenia and unclassified Brocadiaceae were detected with low relative abundances, whereas Geobacteraceae dominated in the treatment throughout the incubation. 15N2 production rates significantly positive correlated with relative abundances of Geobacter, unclassified Geobacteraceae and Anammox bacteria, revealing contribution of them to nitrogen generation via Feammox. Overall, these findings suggested Anammox bacteria or cooperation between Anammox bacteria and iron(III) reducers serve a potential role in Feammox process.